Fracture of the radial proximal epiphysis. A case presentation. - Yusimy Izaguirre Martínez; José Julio Requeiro Molina; Hugo Jiménez Vázquez; Ana María Machado Consuegra (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2005)
Here is presented a case of a patient of 10 years old who while playing football fell down and suffered an epiphysiolysis of the radial cupola, according to the lesion mechanism described by Jeffrey. Before such a lesion, the clinic scheme is exposed and the adequate procedure taken.